2008
DOI: 10.1055/s-2008-1027256
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Intraocular Pressure and Corneal Biomechanical Properties Measurements by the Ocular Response Analyser

Abstract: ORA measurements show good short-term repeatability in normal volunteers. Thus, this device appears to be applicable in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 11 publications
3
27
0
1
Order By: Relevance
“…18 The intrasession repeatability of GAT and IOPg measurements have generally been found to be within about 2 mm Hg. [18][19][20][21][22][23][24] In addition, inter-examiner variability or bias is an issue that is theoretically eliminated with the use of an objective assessment of IOP such as ORA-generated IOPg that would eliminate the need for masked IOP assessment protocols in the research setting. In a population-based epidemiologic study, Dielemans et al 19 investigated GAT test-retest reliability and found a mean intra-observer variation of 1.64 mm Hg and inter-observer variation of 1.79 mm Hg.…”
Section: Discussionmentioning
confidence: 91%
“…18 The intrasession repeatability of GAT and IOPg measurements have generally been found to be within about 2 mm Hg. [18][19][20][21][22][23][24] In addition, inter-examiner variability or bias is an issue that is theoretically eliminated with the use of an objective assessment of IOP such as ORA-generated IOPg that would eliminate the need for masked IOP assessment protocols in the research setting. In a population-based epidemiologic study, Dielemans et al 19 investigated GAT test-retest reliability and found a mean intra-observer variation of 1.64 mm Hg and inter-observer variation of 1.79 mm Hg.…”
Section: Discussionmentioning
confidence: 91%
“…1 Up until recently, the only device conducting in vivo measurements of the ocular biomechanical properties has been the Ocular Response Analyzer (ORA, Reichert Ophthalmic Instruments, Depew, New York, USA) which became commercially available in 2005. 2,3 With the introduction of ORA, an emphasis has been laid on the biomechanical measurements of the cornea in glaucoma diagnosis and in the assessment of the outcomes of refractive surgeries and corneal collagen cross-linking therapies. [4][5][6][7][8][9][10][11] Already the first publication reported differences in the parameters measured with ORA in healthy and keratoconus eyes and in those subsequent to refractive surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the only device which conducted in vivo measurements of the ocular biomechanical properties was the Ocular Response Analyzer (ORA, Reichert Ophthalmic Instruments, Depew, New York, USA), which has been available since 2005 [2,3].…”
Section: Introductionmentioning
confidence: 99%